Fiberoptic Microcatheter-assisted 360-Degree Trabeculotomy Ab Externo After Unsuccessful Trabeculotome Trabeculotomy in Primary Congenital Glaucoma: A Case Report. Issue 8 (August 2016) - D'Amelio, Savino; Gremmo, Giulia; Gremmo, Enrico; Demasi, Christian L.
Abstract : Fiberoptic microcatheter-assisted 360-degree trabeculotomy ab externo is a recent technique. Retrospective studies have proved the effectiveness as a first-angle surgery in eyes with primary congenital glaucoma. However, there are no reports in which it is performed after another unsuccessful surgical procedure. We present our case of a monolateral congenital glaucoma. We first performed an ab externo trabeculotomy with poor control of intraocular pressure (IOP). Then, a microcatheter-assisted 360-degree trabeculotomy was performed with IOP lowering. Microcatheter-assisted 360-degree trabeculotomy supplies successful IOP lowering after another angle surgery procedure.